Faktor Penentu Suksesnya Pengajaran Online Pada Masa New Normal - Martini, Ida Ayu Oka; Dimastari, Ni Nyoman; Adriati, I Gst Ayu Wirati; Sutrisni, Ketut Elly (Jurnal Pendidikan Ekonomi Undiksha, 2022)
Before the pandemic, teaching and learning activities were carried out offline with the guidance of teachers. However, after the Covid-19 pandemic, all teaching and learning activities and extracurricular activities were carried out online. In implementing online learning activities, Pedungan State Elementary School 11 can carry out online learning activities successfully, so it is necessary to study what factors influence the success of online teaching. This research was conducted to find out what factors influence the success of online teaching during the New Normal period at 11 Pedungan State Elementary School. This study uses a qualitative method where this study contains a description of the factors that influence the success of online teaching in the new normal period at 11 Pedungan State Elementary School. Informants in this study were principals, teachers, and parents of students using incidental techniques. The factors that influence the success of online teaching during the new normal period at the 11 Pedungan State Elementary School are as follows: (1) Teacher readiness. Teachers are very ready and have the ability to use information technology. (2) School Readiness. The school has well facilitated this online teaching and learning activity. Such as the internet, computers, laptops, cellphones, special IT rooms. (3) Student Readiness. The students have followed the online learning activities well. according to the schedule determined by the teachers. (4) Readiness of Parents of Students. Parents of students have provided guidance and supervision to their sons and daughters so that online learning can run well.